Woman´s Emotions as an Advertising Strategy of the Pharmaceutical Field at the Beginning of the 20th Century in Chile (2020)
This article aims to reflect on how emotions were part of the expansion of the pharmaceutical field in the early twentieth century in Chile. To introduce the consumption of medicines at home, different pharmacies and apothecaries advertised their remedies in magazines like Family. Two important events took place: first, the gradual use of emotions in drug advertisements and second, the constant use of women in this strategy. Through her, as a woman and mother, and the different moral obligations inscribed in such roles, that we believe that the medicalization of the family needed some emotional argument for the expansion of the pharmaceutical field.